Does Combining Osteophyte Excision and Soft Tissue Release with Total Hip Arthroplasty Enhance Postoperative Functional Recovery and Clinical Outcomes in Crowe Type II–III Dysplastic Hip Osteoarthritis Patients? A Retrospective Comparative Clinical Study - Nizami Mammadov (Orthopedic Surgery and Trauma Journal, 2026)
Background and Aim: Total hip arthroplasty in dysplastic hip osteoarthritis is a complex and challenging procedure. Osteophyte excision and soft tissue release in this cohort study group was combined with total hip arthroplasty to improve postoperative functional recovery and clinical outcomes. The aim of this study is to comparatively evaluate the clinical and functional outcomes of patients undergoing standard total hip arthroplasty and those undergoing combined surgical procedures. Materials and Methods: A total of 135 hips that underwent total hip arthroplasty for dysplastic osteoarthritis between 2017 and 2019 were retrospectively analyzed (control group n=43, combined surgical group n=92). A total of 135 hips that underwent total hip arthroplasty for dysplastic osteoarthritis between 2017 and 2019 were retrospectively analyzed (control group n=43, combined surgical group n=92). Patients were evaluated preoperatively (Pre-op) and at 12 months postoperatively (Post-op) using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), Visual Analog Scale (VAS), Merle d’Aubigné–Postel (MAP) score and Harris Hip Score (HHS). Results: In both groups, statistically significant improvements were observed in range of motion, pain level, functional status, and clinical symptoms parameters during the post-op period compared to the pre-op values . In between groups comparison, both groups were found to be similar in terms of improvement in clinical and functional scores. However, in the combined surgical group, despite more advanced deformities in the pre-op period, post-op clinical and functional outcomes were comparable to the control group. Conclusion: Combining total hip arthroplasty with osteophyte excision and soft tissue release may further enhance postoperative functional recovery and clinical outcomes, particularly in patients with Crowe type II–III deformities.